Konsekuensi Hukum Dan Perlindungan Hak Dalam Perkawinan Beda Agama Di Indonesia - Herli Antoni (Universitas Katolik Widya Karya Malang, 2023)
Marriage between two people who have different religions is prohibited by almost all religions in Indonesia. Even though efforts have been made to obtain legal marital status, when a marriage is carried out, it is still obligatory to pay attention to Article 2 of Law Number 1 of 1974 concerning Marriage. The existence of an official registration in the form of a marriage certificate cannot be overlooked, because without it, marriages that are valid but not registered will not be recognized by the State. Marriage without legal recognition certainly has legal consequences, especially if it involves partners with different religions. This can create significant legal problems for husbands, wives and third parties, including the inheritance rights of children born in the marriage. The existence of a legal marriage is the basis of rights and obligations between husband and wife. The existence of a legally valid marriage and offspring born from a legal marriage are crucial to protecting the wife's rights regarding joint living and property. This is because, as stipulated in Article 43 Paragraph (1) of the Marriage Law, children born from illegitimate marriages only have legal ties with their mothers.